MARTYRDOM AND THE PROCESS OF RADICALISATION AMONG YOUNG MUSLIMS IN INDONESIA: SOCIAL IDENTITY THEORY PERSPECTIVE - Syafiq, Muhammad (Jurnal Psikologi Teori dan Terapan, 2011)
The phenomena of suicide attacks targeting overseas people or properties in Indonesia carried out by Indonesian young Muslim seem to be elusive. Different to Palestinian and Middle Eastern contexts where acute conflicts are taking place, there were no celebrations to martyrdom in Indonesia. Majority of Indonesian Muslims not only reject suicide bombing or martyrdom but also condemn it. Indonesian suicide bombers' families, that is not like those of Palestinian martyrs, were not proud of their member's deed and will not get pride from their neighbourhood. They will not get financial advantages because of family's member sacrifice as well. So, what are the reasons that make Indonesian young Muslims chose to die as a martyr? This article aims to explain the process of radicalisation among young Muslims and reveals the causes and backgrounds of young martyrs in Indonesia based on Social Identity Theory (SIT). Findings of many studies on religious motivated violent attacks are used as comparisons.